PREVENTION OF Staphylococcus aureus CAUSING SKIN DISEASE BY Polianthes tuberose - PRUSTY, SUJATA; ROUT, KRUTANJALI; NAIK, CHINMAYEE; PANDEY, MUKUNDJEE; BHATTACHARYAY, DIPANKAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Phytochemicals are biologically active non-nutritive compounds found in the plants. It has been reported that Polianthes tuberosa plant extract contains different phytochemicals that are traditionally used to cure skin disease. Skin disease is caused by Staphylococcus aureus. Two key enzymes like L-lactate dehydrogenase and IMP dehydrogenase are involved in the biochemical pathway. “Biovia Discovery Studio” was used for studying the molecular docking of the phytochemicals with the enzymes. The strength of the interaction was evaluated based on “-CDOCKER energy and-CDOCKER interaction energy”. High positive values for both the parameters indicated that on protein database code 3D4P, phytochemicals like Kameferol 3-o and Alpha-d glucoside can “effectively deactivated” the L-lactate dehydrogenase enzyme and on protein database code 6I0O, Kameferol 3-o can effectively deactivate the IMP “dehydrogenase enzyme” thereby interrupting the life cycle of Staphylococcus.